Kebijakan Pemerintah Kabupaten Tasikmalaya dalam Meningkatkan Kualitas Pendidikan Menuju Indonesia Emas 2045 - Yunita, Rosi; Yuliawati, Fitriyani; Sarofah, Riska (Faculty of Social and Political Science, Universitas Siliwangi, 2025)
This study aims to analyze the Tasikmalaya Regency government's policy in improving the quality of education towards Golden Indonesia 2045. Education has a strategic role in forming superior human resources as the main foundation of regional development. Tasikmalaya Regency as one of the regions with great potential in West Java faces various challenges in improving the quality of education, including the still low achievement of Average Years of Schooling. This study aims to analyze the actual condition of education in Tasikmalaya Regency, identify problems and their root causes, and develop effective and sustainable policy strategies in order to improve the quality of education towards Golden Indonesia 2045. The study uses a qualitative-descriptive approach with a policy analysis method. The data used are secondary data from literature reviews and literature studies. The results of the study indicate that increasing the average school as an effort to improve the quality of education in Tasikmalaya Regency requires an integrated policy based on five main pillars: (1) Equitable Access and Educational Infrastructure; (2) Strengthening Family Economic Support; (3) Prevention and Handling of School Dropouts; (4) Relevance of Education to the World of Work; and (5) Strengthening Educational Governance and Policy. The implementation of this strategy is expected to encourage educational transformation in Tasikmalaya Regency that is inclusive, adaptive, and quality-oriented, so that Tasikmalaya Regency can contribute optimally in realizing Golden Indonesia 2045.